Design and Application of Multimodal Communication Scheme Based on Cloud Platform - Wang, Hui; Song, Jie (Journal of physics. Conference series, 2020)
Cloud computing platforms are the product of modern information technology (IT) development and one of the hottest research directions in the big data era. In this paper, the functions and principles of a multimodal integrated communication notification system that combines the communication methods such as e-mail, mobile phone text messages and voice calls are expounded, focusing on the discussion of JMail components, reliable mass texting, short message encoding/decoding, and other core technologies in the cloud-based system design. How to use JMail object, ADO, and multi-threading technologies to implement complex tasks such as information mass texting, fast receiving, processing, and recovery requires further study. Experiments suggest that the proposed method can solve the difficulties in designing information mass texting and reliability in design effectively.